Juridical Analysis on Loading Acquisition of Land And Buildings (BPHTB) on The Transfer of Land And Building to Taxpayers in Pekalongan - Bella Bestharinda Anjani; Meilyna Dwijanti; Djauhari Djauhari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Taxes as a source of revenue for the state should be a great reception because the source another in come. One type of tax is BPHTB imposed on taxpayers individuals or legal entities that transfer of land rights. Methods of using juridical empirical approach, analytical descriptive specification. Source data using primary data and secondary data, engineering data collection is by interview, documentation and literature, data analysis done qualitatively. The results showed that: 1) The amount of taxes payable in SKBKB will be subject to an administrative penalty of 2% calculated from tax under or over for a maximum period of 24 months from the date the tax is due, but if the taxpayer to report it / then not be subject to administrative sanctions ; 2) The application of tax rates on Acquisition of Land and Building is 5% (five percent); 3) Role the PPAT in giving the services to the people in application of making the land certificate based on the regulation and become registated in PPAT.Keywords: Cost, Supply Customs Land and Building (BPHTB), Taxpayer.